The Role of Organizational Resilience in the Influence of Transformational Leadership and Employee Engagement on Organizational Performance - Agustinus Setyawan; Rieza Melinda; Alden Nelson (Dinasti Publisher, 2025)
The main objective of this study is to investigate how transformational leadership and employee engagement impact organizational performance in the logistics industry, with organizational resilience as a mediator. Using quantitative method, this study focuses on hypothesis testing. The study population consists of managerial level employees of logistics companies in Batam. Sample selection involved proportional representation of employees across different companies in the industry. Hypothesis testing showed significant relationships between the variables, with support for five of the seven hypotheses, consistent with previous research and offering empirical validation for the relationships examined. R-square values indicate a moderate relationship, suggesting that organizational performance is strongly influenced by organizational resilience, and vice versa, although other factors may also contribute to this dynamic.